Adaptation and validation of selected stroke accuracy tests for elite Para table tennis players - Galasa, S.; Plutaa, B. (Acta Kinesiologica, 2025)
Purpose: To adapt and validate selected tests assessed the accuracy and precision of flip shots and bottom spin backhand strokes precision hitting for Para table tennis players: Manual quickness & ability Forehand (Manual Q&A FH), Manual quickness & ability Beckhand (Manual Q&A BH), Alternate push test.